2013
DOI: 10.1074/jbc.m112.431155
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 1-mediated Effects of Exercise and Resveratrol on Mitochondrial Biogenesis

Abstract: Background: SirT1 regulates mitochondrial biogenesis in various tissues. Results: Exercise combined with resveratrol has a SirT1-dependent synergistic effect on mitochondrial biogenesis, despite individual treatments being SirT1-independent. Conclusion: SirT1 is important for maintaining muscle mitochondrial content and function. Significance: The dependence of muscle mitochondrial biogenesis on SirT1 depends on the metabolic state of the muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
133
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(151 citation statements)
references
References 57 publications
(63 reference statements)
10
133
1
1
Order By: Relevance
“…RSV is known to improve energy homeostasis [16] and so we hypothesized that the mechanism of the positive effects of RSV on the myogenicity of satellite cells is linked to mitochondrial function. This hypothesis also implies that a decline in mitochondrial activity is one of the key causes of poor regenerative performance of muscle stem cells in a diabetic environment.…”
Section: Mitochondrial Membrane Potential Is Diminished In Muscle Stementioning
confidence: 99%
See 1 more Smart Citation
“…RSV is known to improve energy homeostasis [16] and so we hypothesized that the mechanism of the positive effects of RSV on the myogenicity of satellite cells is linked to mitochondrial function. This hypothesis also implies that a decline in mitochondrial activity is one of the key causes of poor regenerative performance of muscle stem cells in a diabetic environment.…”
Section: Mitochondrial Membrane Potential Is Diminished In Muscle Stementioning
confidence: 99%
“…One of the targets of Sirt1 is PGC-1α, which positively regulates mitochondrial biogenesis and function. Interestingly, studies in mice with a muscle-specific Sirt1 knockout suggest that Sirt1 is not involved in RSV-induced mitochondrial biogenesis in muscle cells, indicating that other targets of RSV must be responsible for the positive effects of RSV on skeletal muscle metabolism [16].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent and parallel work of others has further solidified this theory (2,5,6,17,26,31,40,57). Studies aimed at deciphering the mechanisms involved in controlling the slow, oxidative phenotype in dystrophic skeletal muscle are important as they pave the way for target identification and rational design of specific interventions focused on ameliorating the pathology of DMD via pharmacological agents.Chronic administration of the naturally occurring polyphenol resveratrol (RSV) to numerous experimental, nondystrophic rodent models has revealed that this compound elicits the slow, oxidative myogenic program in skeletal muscle and ameliorates myopathies associated with high-fat feeding and muscle unloading, potentially through an AMPK-sirtuin 1 (SIRT1)-peroxisome proliferator-activated receptor-␥ coactivator-1␣ (PGC-1␣)-dependent web of intracellular signaling (1,3,4,14,18,30,33,34,35,42,45,49,52,59). Notably, this latter point is cause for debate (24,25,28,50,51,61).…”
mentioning
confidence: 99%
“…Skeletal muscle mitochondrial function (Yamamoto et al ., 2011), mitochondrial biogenesis (Irrcher et al ., 2003), and resistance to oxidative stress (Nishiyama et al ., 1998; Fisher‐Wellman et al ., 2009; Ryan et al ., 2010) were also examined, as these mechanisms mediate exercise performance (Rockl et al ., 2007). The SIRT1, FOXO3a, and MEK pathways, key to mitochondrial biogenesis and protection against oxidative stress, were also examined (Wu et al ., 1999; Lagouge et al ., 2006; Gurd et al ., 2009; Menzies et al ., 2013; Li et al ., 2015; Smith et al ., 2015). As one of the most potent mechanisms limiting longevity is increased oxidative stress (Gemma et al ., 2007), MnSOD levels were examined and exercise was examined in AC5 KO mice mated with MnSOD heterozygous ( MnSOD +/− ) mice.…”
Section: Introductionmentioning
confidence: 99%